Geriatric Assessment in Elderly People by Using ABCDE (Ability Balance Cognitive Diseases Emotion) Method at Posyandu for Elderly People - Nunik Sulistyaningsih; Mora Claramita; I Dewa Putu Pramantara (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2021)
Background: Elderly populations have increased in line with the increased life expectancy. Currently, the balance of disease burden on the elderly has shifted towards chronic disease. Cardiovascular disease, diabetes, cognitive impairment and depression are chronic diseases that cause suffering and death in elderly populations. Therefore, it is necessary to conduct a comprehensive and multidimensional health assessment as a preventive effort to reduce morbidity in the elderly.Objective: The general objective of this research was to obtain a description of elderly health status at the Posyandu for the elderly using a geriatric assessment called the ABCDE (Ability, Balance, Cognitive, Diseases, Emotion) method.Methods: This research used a cross-sectional design. The subjects were elderly persons ≥ 60 years old who participated in the Posyandu for the elderly and who had fulfilled inclusion and exclusion criteria. The estimated minimum sample size was 242 selected using stratified random sampling. The statistical analysis in this research employed univariate, and bivariate analysis using Chi square tests.Results: Elderly participants had light dependency (34.2%) with average activities of daily living (ADL) value of 19.39 ± 1.32, positive Romberg test 3.7%, and Sharpened Romberg Test 50%. The prevalence of cognitive impairment was 43.4%, while the average score of Mini Mental State Examination was 23.31 ± 6.08, hypertension prevalence 73.14%, hypercholesterolemia 13.22%, and diabetes mellitus 10.33%. Elderly who had depression and probable depression were 12.81%, consisting of mild depression 11.57% and moderate depression 1.24%. Balance disorders had a statistically significant correlation with ADL (p = 0.012; Ratio Prevalence (RP) = 1.422: 95% CI), cognitive impairment (p = 0.039; RP = 1.31: 95% CI), and depression (p = 0.034; RP = 1.63: 95% CI).Conclusion: The prevalences of hypertension, cognitive impairment, and balance disorder on sharpened Romberg test were high. There were statistically significant correlations between balance disorder and ADL, cognitive function, and depression. These findings support the application of geriatric assessment by using ABCDE which can be applied in primary care setting for elderly people.